2016 Children's Tumor Foundation conference on neurofibromatosis type 1, neurofibromatosis type 2, and schwannomatosis. Issue 5 (21st April 2018) - Fisher, Michael J.; Belzberg, Allan J.; de Blank, Peter; De Raedt, Thomas; Elefteriou, Florent; Ferner, Rosalie E.; Giovannini, Marco; Harris, Gordon J.; Kalamarides, Michel; Karajannis, Matthias A.; Kim, AeRang; Lázaro, Conxi; et al.
Abstract : Organized and hosted by the Children's Tumor Foundation (CTF), the Neurofibromatosis (NF) conference is the premier annual gathering for clinicians and researchers interested in neurofibromatosis type 1 (NF1), neurofibromatosis type 2 (NF2), and schwannomatosis (SWN). The 2016 edition constituted a blend of clinical and basic aspects of NF research that helped in clarifying different advances in the field. The incorporation of next generation sequencing is changing the way genetic diagnostics is performed for NF and related disorders, providing solutions to problems like genetic heterogeneity, overlapping clinical manifestations, or the presence of mosaicism. The transformation from plexiform neurofibroma (PNF) to malignant peripheral nerve sheath tumor (MPNST) is being clarified, along with new management and treatments for benign and premalignant tumors. Promising new cellular and in vivo models for understanding the musculoskeletal abnormalities in NF1, the development of NF2 or SWN associated schwannomas, and clarifying the cells that give rise to NF1‐associated optic pathway glioma were presented. The interaction of neurofibromin and SPRED1 was described comprehensively, providing functional insight that will help in the interpretation of pathogenicity of certain missense variants identified in NF1 and Legius syndrome patients. Novel promising imaging techniques are being developed, as well as new integrative and holistic management models for patients that take into account psychological, social, and biological factors. Importantly, new therapeutic approaches for schwannomas, meningiomas, ependymomas, PNF, and MPNST are being pursued. This report highlights the major advances that were presented at the 2016 CTF NF conference.